2022
DOI: 10.1038/s41598-022-12024-8
|View full text |Cite
|
Sign up to set email alerts
|

Variational autoencoder provides proof of concept that compressing CDT to extremely low-dimensional space retains its ability of distinguishing dementia

Abstract: The clock drawing test (CDT) is an inexpensive tool to screen for dementia. In this study, we examined if a variational autoencoder (VAE) with only two latent variables can capture and encode clock drawing anomalies from a large dataset of unannotated CDTs (n = 13,580) using self-supervised pre-training and use them to classify dementia CDTs (n = 18) from non-dementia CDTs (n = 20). The model was independently validated using a larger cohort consisting of 41 dementia and 50 non-dementia clocks. The classificat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…For instance, a smaller clockface area is associated with subcortical disease profiles with primary executive dysfunction (e.g., micrographia in Parkinson's disease) 9 , and misplacement of clock hands is associated with visual attention deficits and disinhibition 2 . In comparison to a previously published VAE encoding 27 , the RF-VAE encoding reported in this study achieved significantly better results on the same classification dataset using identical training methods. This improvement is due to diversification of the latent space, and disentangling the latent dimensions.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…For instance, a smaller clockface area is associated with subcortical disease profiles with primary executive dysfunction (e.g., micrographia in Parkinson's disease) 9 , and misplacement of clock hands is associated with visual attention deficits and disinhibition 2 . In comparison to a previously published VAE encoding 27 , the RF-VAE encoding reported in this study achieved significantly better results on the same classification dataset using identical training methods. This improvement is due to diversification of the latent space, and disentangling the latent dimensions.…”
Section: Discussionmentioning
confidence: 47%
“…The feed-forward neural network classifier combines these features in a non-linear way to discriminate dementia from controls. A previous study attempted to classify dementia from non-dementia using a two-dimensional latent space VAE network 27 . This work provided proof of concept that compressed CDT representations retain their ability to distinguish dementia.…”
Section: Introductionmentioning
confidence: 99%
“…The horizontal and vertical placement of the drawing in the space provided loaded on other factors. Using a relevance factor variational autoencoder (RF-VAE), a deep neural network, Bandyopadhyay et al (2022) found that an irregularly drawn clock face was able to distinguish between dementia versus non- dementia patients. As described above, Dion et al (2022) found that errors in number placement was associated with poorer performance on selected neuropsychological tests and negatively associated with connectivity from the basal nucleus of Meynert (BNM) to the anterior cingulate cortex (ACC).…”
Section: Discussionmentioning
confidence: 99%
“…While hybrid architectures of Variational Autoencoder (VAE)-based unsupervised learning and classifier module have been investigated for solving classification tasks with limited labeled data and a large number of non-labeled data 78 , 79 , their application to dimensionality reduction and feature extraction has been studied more recently. For example, Bandyopadhyay et al 56 utilized this architecture to extract features from drawings by dementia patients to distinguish between dementia and non-dementia cases. Similar architectures have been extended to handle multimodal inputs for anomaly detection in robotic vehicles under uncertain environments 55 , or for classification of diverse cancer types using omics data 57 .…”
Section: Discussionmentioning
confidence: 99%